2021
DOI: 10.1101/2021.06.21.21259231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A thematic analysis of Prison and Probation Ombudsman fatal incident reports involving prisoners on palliative/end-of-life care pathways in the long-term high security estate in England and Wales

Abstract: Objectives In this study, the clinical and non-clinical factors that may influence the provision of palliative/end of life care in long-term high security prisons in England and Wales are identified through the lens of Prison and Probation Ombudsman (PPO) fatal incident reports. Methods This work extends that of McParland and Johnston (2019) and contemporary literature published in the subsequent period to 2020 through a thematic analysis of fatal incident reports published by the PPO in the period 2014-202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…As Tomczak (2022, p. 500) argues, 'these detailed, publicly available documents are an underutilized data source, providing extensive information about deaths, prisons, and responses to prison deaths over time.' PPO fatal investigation reports have been analysed to explore self-inflicted deaths or deaths by suicide (Tomczak, 2018) domestic violence perpetration and suicide risk in males imprisoned (Dewar, 2018) and natural cause deaths involving palliative care (Kirkham, 2021). To our knowledge, the research reported here is the first time that they have been used to analyse substance-related deaths.…”
Section: The Role Of the Prison And Probation Ombudsman And Fatal Inc...mentioning
confidence: 99%
“…As Tomczak (2022, p. 500) argues, 'these detailed, publicly available documents are an underutilized data source, providing extensive information about deaths, prisons, and responses to prison deaths over time.' PPO fatal investigation reports have been analysed to explore self-inflicted deaths or deaths by suicide (Tomczak, 2018) domestic violence perpetration and suicide risk in males imprisoned (Dewar, 2018) and natural cause deaths involving palliative care (Kirkham, 2021). To our knowledge, the research reported here is the first time that they have been used to analyse substance-related deaths.…”
Section: The Role Of the Prison And Probation Ombudsman And Fatal Inc...mentioning
confidence: 99%